2017
DOI: 10.1128/aac.01054-17
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics, Tolerability, and Bacteriological Response of Rifampin Administered at 600, 900, and 1,200 Milligrams Daily in Patients with Pulmonary Tuberculosis

Abstract: In a multiple-dose-ranging trial, we previously evaluated higher doses of rifampin in patients for 2 weeks. The objectives of the current study were to administer higher doses of rifampin for a longer period to compare the pharmacokinetics, safety/tolerability, and bacteriological activity of such regimens. In a double-blind, randomized, placebo-controlled, phase II clinical trial, 150 Tanzanian patients with tuberculosis (TB) were randomized to receive either 600 mg (approximately 10 mg/kg of body weight), 90… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
3
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(66 citation statements)
references
References 22 publications
2
60
3
1
Order By: Relevance
“…To study the possible synergistic effect of antibiotics, NAC and induction heating, the titanium alloy coupons with biofilm were also exposed (after induction heating) to vancomycin (10 mg/l or 1 mg/l) and rifampicin (1 mg/l) with and without NAC (0.5 mg/l, all from Sigma-Aldrich, Chicago, IL) for 24 h at 37 C. These concentrations were chosen to represent clinically relevant concentrations [22][23][24]. To represent clinical practice, we added rifampicin to the antibiotic treatment because the studied S. aureus strain (ATCC 29213) is sensitive to rifampicin [25,26].…”
Section: Heat Antibiotics and Nac Experimentsmentioning
confidence: 99%
“…To study the possible synergistic effect of antibiotics, NAC and induction heating, the titanium alloy coupons with biofilm were also exposed (after induction heating) to vancomycin (10 mg/l or 1 mg/l) and rifampicin (1 mg/l) with and without NAC (0.5 mg/l, all from Sigma-Aldrich, Chicago, IL) for 24 h at 37 C. These concentrations were chosen to represent clinically relevant concentrations [22][23][24]. To represent clinical practice, we added rifampicin to the antibiotic treatment because the studied S. aureus strain (ATCC 29213) is sensitive to rifampicin [25,26].…”
Section: Heat Antibiotics and Nac Experimentsmentioning
confidence: 99%
“…This led to a phase II open-label randomized controlled trial evaluating the efficacy of daily RIF at 600, 900, and 1,200 mg for 2 months with the primary endpoints of assessing safety and tolerability. 29 Bacteriologic clearance was not different among the study arms; however, a follow-up study evaluating a combination of RIF doses with or without moxifloxacin or SQ109 found faster time to culture conversion in participants receiving 35 mg/kg doses of RIF. 30 In vitro studies, animal models, and human studies suggest rifapentine (RPT) may have increased bactericidal activity compared with RIF.…”
Section: Drug-susceptible Tuberculosismentioning
confidence: 88%
“…Rifampin and rifabutin are commonly used for the treatment of MAC, M kansasii, and other select NTM. 7,53,54 Rifampin is a strong inducer for the hepatic cytochrome (CYP) enzyme system, (eg, strong inducer for CYP3A4 and CYP2C19; moderate inducer for CYP2B6, CYP2C8, and CYP2C9; weak inducer for CYP1A2) and an inducer for the P-glycoprotein pathway. Rifabutin induces CYP3A4 to a lesser extent compared with rifampin.…”
Section: Rifamycinsmentioning
confidence: 99%